PEMBUATAN DAN UJI ORGANOLEPTIS SEDIAAN BEDAK DINGIN DARI JAGUNG MANIS (Zea mays Sacchrata) DAN TEPUNG BERAS (Oriza sativa L) - Pramesti, Bunga Delima; Handayani, Reti Puji; Nuraini, Sitti Sarah (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2018)
Background: Acne is a skin problem that almost struck any person, however, the use of skin care products containing chemicals can not be avoided. Objective: This study aims to make dosage cold powder and determine the stability of the dosage cold powder of sweet corn (Zea mays Sacharata) and rice (Oryza sativa L.) for 3 weeks. Method: This study uses action research design testing the formulation of two different solvents. Result: The results showed that the samples with the solvents distilled water there is no change in color, scent as well as stable in the storage period of three weeks. The results of pH testing meet the requirements of the pH to the face is 4-6. As for dosage forms with solvents of rose water containing oleum rosae tend to be more moist because it contains oil which is harder to evaporate so that changes in color, odor, pH and appear fungus. Conclusion: From the results of the study concluded that the manufacture of dosage forms with the solvents distilled water is stable, no color change, scent trademark, pH stable and not found the mushrooms during storage for three weeks. It is recommended to do more research with the drying time is longer.